2019
DOI: 10.3389/fonc.2019.00563
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for IL-35 Expression in Diffuse Large B-Cell Lymphoma and Impact on the Patient's Prognosis

Abstract: IL-35 is an immunosuppressive cytokine of the IL-12 family consisting of two subunits, EBV-induced gene 3 (EBI3) and p35. It has been shown to play a pro-tumor role in murine tumor models, and in various types of human cancer such as colorectal, pancreatic, or liver carcinoma, its expression has been associated with a worse clinical outcome. Here, we show by analyzing gene expression data from public databases and by immunohistochemical studies that IL-35 is overexpressed by tumor cells in diffuse-large B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…When the IL-12Rβ1 subunit is combined with the Ebi3 subunit, it becomes an immunosuppressive unit activated by IL35 35 . IL-35, a pro-tumor member of the IL12 cytokine family, is overexpressed in DLBCL 36 and suppresses naive T-cell activation 37 . In a phase II clinical trial for non-Hodgkin's Lymphoma and Hodgkin's Lymphoma, IL12 administration increased circulating CD8+ T-cell presence but had no effect on CD4+ T-cell presence 38 .…”
Section: Discussionmentioning
confidence: 99%
“…When the IL-12Rβ1 subunit is combined with the Ebi3 subunit, it becomes an immunosuppressive unit activated by IL35 35 . IL-35, a pro-tumor member of the IL12 cytokine family, is overexpressed in DLBCL 36 and suppresses naive T-cell activation 37 . In a phase II clinical trial for non-Hodgkin's Lymphoma and Hodgkin's Lymphoma, IL12 administration increased circulating CD8+ T-cell presence but had no effect on CD4+ T-cell presence 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies reported elevated levels of circulating IL-35 in breast cancer patients, which positively correlated with the expression of Ki67, p53 and EGFR on breast cancer cells [ 192 ]. Furthermore, high levels of IL-35 were shown to be associated with the poor survival of diffuse-large B-cell lymphoma (DLBCL) patients treated with chemotherapy [ 193 ]. Additionally, increased levels of IL-35 were observed in the bone marrow of acute myeloid leukemia (AML) patients and correlated positively with clinical stages [ 194 ].…”
Section: Introduction Il-12 Family Cytokines: Composition Signalmentioning
confidence: 99%
“…This suggests that in wild-type mice, the EBI3 subunit might preferentially dimerize with the IL-12p35 subunit to form the anti-inflammatory cytokine IL-35. Although attempts were made to clarify the binding partner of EBI3 by co-immunoprecipitation, this proved unfeasible owing to the near identical sizes of IL-12 family members and the known lack of reliable commercial antibodies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%